Relationship between Mast Cells and the Colitis with Relapse Induced by Trinitrobenzesulphonic Acid in Wistar Rats - Ana Carolina Luchini; Déborah Mara Costa de Oliveira; Cláudia Helena Pellizzon; Luiz Claudio Di Stasi; José Carlos Gomes (Mediators of Inflammation)
The present study aimed to clarify the role of mast cells in colitis with relapse induced in Wistar rats by trinitrobenzenosulphonic acid. Colitis induction increased the histamine concentration in the colon, which peaked on day 26. The number of mast cells, probably immature, was ten times higher on day 8. Different from animals infected with intestinal parasites, after colitis remission, mast cells do not migrate to the spleen, showing that mast cell proliferation presents different characteristics depending on the inflammation stimuli. Treatment with sulfasalazine, doxantrazole, quercetin, or nedocromil did not increase the histamine concentration or the mast cell number in the colon on day 26, thereby showing absence of degranulation of these cells. In conclusion, although mast cell proliferation is associated with colitis, these cells and their mediators appear to play no clear role in the colitis with relapses.